Profitability and Firm Value in the Perspective of Signaling Theory and Stakeholder Theory: The Moderating Role of Sustainability Reporting - Revi Candra; Nurul Nazifah; Gampito; Elfadhli; Fatimah Setia Wardani (Yayasan Ilomata, 2026)
The increase in profitability does not automatically lead to a higher firm value, indicating that other supporting factors may influence this relationship. One factor frequently associated with strengthening this linkage is sustainability reporting, which reflects a company’s commitment to transparency and responsibility toward its stakeholders. Accordingly, this research investigates how profitability affects firm value and examines whether sustainability reporting moderates this relationship in plantation companies listed on the Indonesia Stock Exchange during the 2021–2023 period. This study differs from prior research in mining or other ESG-sensitive sectors by addressing the unique land-use legitimacy challenges of the plantation industry, where a conditional moderation model is theoretically essential to explain how sustainability disclosure reconfigures the interpretation of financial signals. This research applies a quantitative research design with a causal approach. The population includes 24 plantation sector companies, from which 11 firms that consistently publish sustainability reports were selected using a purposive sampling technique. The data analysis was conducted through classical assumption testing followed by Moderated Regression Analysis (MRA). The findings reveal that profitability and sustainability reporting individually exhibit negative and significant effects on firm value. However, the interaction term shows a positive and significant coefficient, indicating a conditional moderating effect. This suggests that sustainability reporting strengthens the influence of profitability under certain conditions rather than directly increasing firm value. Unlike previous studies that focus solely on the linear relationship between profitability and firm value, this research examines the specific nuances of ESG-sensitive industries through a moderation lens.